Seasonal hydrological and suspended sediment transport dynamics and their future modelling in the Orwell Glacier proglacial stream, Signy Island, Antarctica. Issue 2 (April 2021) - Stott, Tim; Convey, Peter
Abstract: Climate change in the Antarctic over the past 50+ years has caused contraction of ice and snow cover, longer melt seasons and intensified glacier melting. These changes affect erosion and sediment redistribution processes that are vital to our understanding of terrestrial and freshwater ecosystems and sediment input to oceans. This 79 day study of the Orwell Glacier meltwater stream on Signy Island (5 December 2019–21 February 2020) used 5 min recordings of turbidity, stream discharge (Q) and air temperature (AT), supplemented by 454 water samples from which suspended sediment concentration (SSC) was gravimetrically determined, to calculate daily suspended sediment loads (SSLs). Qmean was 47.8 ± 3.5 l s -1, SSCmean was 71.0 ± 15.9 mg l -1 and daily SSLmean was 75 ± 8 kg day -1 with a suspended sediment yield of 43.6 t km -2 yr -1 . A multiple regression model predicted SSLs reliably (multiple r = 0.95, r 2 = 0.91, n = 79) and, when run with ATmean + 1°C (expected on Signy Island by 2060) and ATmean + 2°C (expected by 2100) scenarios, the model predicted 7% and 13% increases in SSLs, respectively. The SSLs estimated in this study are low when compared with others from around the world.